THE EFFECTIVENESS OF SOCIAL MEDIA ON HYPERTENSION SELF-MANAGEMENT: A SYSTEMATIC REVIEW - Risah Bellah Susanto; Ira Nurmala; Mohammad Zainal Fatah (Jurnal Endurance, 2023)
Hypertension is a non-communicable disease characterized by high blood pressure at rest, systolic blood pressure of 140 mmHg, and diastolic blood pressure of 90 mmHg and above and repeated measurements have been made a maximum of 2-3 times. The purpose of this study was to determine the effectiveness of social media on hypertension self-management. This study is a systematic journal using the preferred item reporting method for systematic and meta-analysis (PRISMA) using 459 articles from an online database. The databases used in the library search were Scopus, Sage, Pubmed, Proquest, and Worldcat from 2018-2022. Based on the inclusion and exclusion characteristics, there were 8 out of 459 articles that met the inclusion criteria, and were selected for in-depth analysis. Information through social media has an impact on hypertension self-management. Suggestions for further researchers to be able to more broadly examine the effectiveness of social media on self-management of hypertension, especially in the elderly in Indonesia, as well as researchers hope that doctors and nurses can develop educational programs for patients to support self-management behavior of patients with chronic diseases who use social media, by The goal is to make it easier to convey messages or information. Keywords: Social Media, Self Management, Hypertension, Good Health